2012
DOI: 10.5424/sjar/2012102-341-11
|View full text |Cite
|
Sign up to set email alerts
|

Effect of extruded whole soybean dietary concentrate on conjugated linoleic acid concentration in milk in Jersey cows under pasture conditions

Abstract: Contradictory results has been found on the effects of soybean supplementation and conjugated linoleic acid (CLA) content in milk on feeding systems based on fresh forage The objective of the study was to evaluate the effect of a dietary supplement with different quantities of extruded whole soybean on the production and composition of milk, and CLA concentration or their isomers in Jersey cows under pasture conditions. Twenty-one Jersey cows were randomly assigned into 3 groups of 7 animals each. The cows wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 37 publications
1
9
0
4
Order By: Relevance
“…In the present study, in agreement with the results found in a previous work by Avilez et al (2012), the trans-10, cis-12 and cis-10, cis-12 isomers presented higher values than normally reported in the literature. The regulation of isomer balance is largely unknown.…”
Section: Cla Content and Compositionsupporting
confidence: 93%
See 4 more Smart Citations
“…In the present study, in agreement with the results found in a previous work by Avilez et al (2012), the trans-10, cis-12 and cis-10, cis-12 isomers presented higher values than normally reported in the literature. The regulation of isomer balance is largely unknown.…”
Section: Cla Content and Compositionsupporting
confidence: 93%
“…All the samples (pasture and concentrates) were ground to pass a 1-mm screen in a Willey mill before analysis. Dry matter (method 934.01), ash (method 942.05), ether extract (method Avilez et al (2012). The analyses of neutral detergent fibre (NDF) and acid detergent fibre (ADF) were carried out according to Van Soest et al (1991), and both NDF and ADF were expressed as exclusive of residual ash.…”
Section: Laboratory Analysesmentioning
confidence: 99%
See 3 more Smart Citations